Characterization of interface reaction of Ti/Al-based ohmic contacts on AlGaN/GaN epitaxial layers on GaN substrate. (21st April 2016) - Zadeh, Daryoush H.; Tanabe, Shinichi; Watanabe, Noriyuki; Matsuzaki, Hideaki
Abstract: The ohmic properties of Ti/Al/Mo/Au contacts on a high-quality AlGaN/GaN heterostructure epitaxially grown on a GaN substrate were investigated. Systematic structural and electrical analyses of the metal/AlGaN interface after annealing in N2 at 700 and 900 °C were conducted. After annealing at 900 °C, a new Al-rich interlayer with nitrogen vacancies was formed at the metal/AlGaN interface. Ohmic contacts with a low specific contact resistance (ρc ) of 5.1 × 10 −6 Ω cm 2 and a dominant field emission carrier transport mechanism were achieved. The fabrication of recessed-AlGaN-structured ohmic contact with ρc as low as 2.4 × 10 −5 Ω cm 2 at a low annealing temperature of 650 °C, was also successfully demonstrated. This result indicates that a process methodology can be provided for fabricating low-resistivity ohmic contacts with a low thermal budget on a high-quality AlGaN/GaN structure, which is based on an appropriate control of the metal/AlGaN interface and AlGaN thickness rather than relying on the existence of threading dislocations.